Antibiotics for the treatment of COVID‐19 - article Editorial (Безопасность и риск фармакотерапии)
This article is the Russian translation of the Plain Language Summary (PLS) of the Cochrane Review previously published in the Cochrane Database of Systematic Reviews. Original publication: Popp M, Stegemann M, Riemer M, Metzendorf MI, Romero CS, Mikolajewska A, et al. Antibiotics for the treatment of COVID-19. Cochrane Database of Systematic Reviews. Version published: 22 October 2021. https://doi.org/10.1002/14651858.CD015025